Development of Indonesian Realistic Mathematics Education-Based Learning Module - Awalimahfuzoh, Rafiqa; Lubis, Marasamin; Siregar, Tanti Jumaisyaroh (Yana Research, 2022)
This study aims to develop teaching materials in the form of Mathematics Modules Based on Indonesian Realistic Mathematics Education (PMRI) on the material of sequences and series in class VIII. The quality of the developed product is assessed based on aspects of the validity, practicality and effectiveness of the developed module. This research method uses the type of Research and Development (Research and Development) using a research design from the Borg and Gall procedure. The subjects of this study were students of class VIII Mts Negeri Labuhanbatu Utara, totaling 20 students. The results obtained are that the development of this module can improve student learning outcomes and understanding. The results of the validity of this module were tested from the validity of media experts and material experts getting an average score of 92.85% in the